Politics of Space in News Media: Mapping Religion in Four Finnish Newspapers (2007–2011) - Sumiala, Johanna (Journal of religion in Europe, 2017)
In this article, we examine religion in the news media by applying a spatial approach. Our content analysis of journalistic reporting on religion is based on a study of four Finnish newspapers over a five-year period. The data shows that the space of religion in the Finnish newspapers comprises complex dynamics connected with place, embedded in journalistic conventions and practices. Journalistic practices and the segmentation into newspaper sections result in a strict separation among local, national, and global themes related to religion, consequently erecting boundaries between inclusion and exclusion, proximity and distance, and centre and periphery associated with the religion in question. We conclude with a reflection on the politics of space and its significance in positioning religion not only in the studied newspapers but also in Finnish society and in Europe at large.